Social Context of Civil Process for Sustainable Development - Kharitonashvili, Nino (European Scientific Journal, ESJ, 2024)
A democratic society develops the concept of a social state, expressed in ensuring equal conditions for the participation of vulnerable persons in civil turnover. At the same time, humanity has agreed on a sustainable development plan, in which social sustainability is set as one of the main goals. Modern civil procedure law is mainly based on the codification of the 19th century, which in turn originates from the "Roman law" created precisely for the citizens of Rome. But since then, public relations have changed and modern technologies are constantly developing. The concept of a digital judge, smart contracts, and a blockchain system has already been developed. Therefore, it is necessary to update the civil procedure legislation to find out how it provides an equal platform for the participation of vulnerable persons in civil disputes. The purpose of this article is to discuss procedures for regulating civil disputes in a social context. As a result of identifying existing gaps, specific recommendations have been developed that will bring civil dispute resolution closer to sustainable development plans and ensure the participation of vulnerable persons in civil disputes on equal terms.